Voices from the Soviet edge : southern migrants in Leningrad and Moscow - Sahadeo, Jeff, 1967- (Cornell University Press, 2019)
"This book focuses on those peoples of the Caucasus and Central Asia, who were making the streets of the Soviet Union's "two capitals" their own. Hundreds of thousands of Uzbeks, Tajiks, Georgians, Azerbaijanis and others arrived in the last Soviet era, seeking opportunity at the privileged heart of the USSR. Using extensive oral histories as well as published and archival sources, this book shows how their energy transformed their own and their family's life chances and created inter-republican networks, altering life in the center and periphery alike. Citizens of the Soviet Union but often lacking residence papers required for their stay; denigrated as "Blacks" by some in the local population but accepted by others for their knowledge and goods; excited by their status as residents of the capital, but torn over attachments to an ethnic identity and home: these newcomers exemplify the ambiguities of the Soviet modernization and multinational project. This book connects Leningrad and Moscow to transnational trends of core-periphery movement and marks them as global cities. It examines Soviet concepts, such as the "friendship of peoples," alongside ethnic and national difference, which became racialized. It reveals the Brezhnev era as a time of dynamism and opportunity, and Leningrad and Moscow not as isolated outposts of privilege, but at the heart of any number of systems that linked the Soviet Union. In the 1980s, the Soviet Union crumbled from the outside in, and increased migration presaged perestroika-era tensions and shortages and, eventually, the USSR's collapse. These migrants were the forbears of the million-plus Muslims from the former Soviet spaces now in Leningrad and Moscow, who have confronted rampant racism in the 2000s"--